Bridging Pedagogy And Practice: Perceptions Of Pre-Service And In-Service Teachers On The Implementation Of Inquiry-Based Learning In DBSE Schools Of Delhi (International Journal of Environmental Sciences, 2025)
This study tries to understand the impact of inquiry-based learning (IBL) pedagogy as perceived by D.El.Ed. trainees (pre-service teachers), in-service school teachers, and teacher educators working under the Delhi Board of School Education (DBSE). In the wake of the National Education Policy (NEP) 2020, the DBSE was introduced in 2021 to promote holistic, competency-driven, and discovery-oriented teaching. However, implementing IBL at the classroom level remains a complex challenge due to infrastructural gaps, teacher preparedness, and student learning readiness. This mixed-method study employed an exploratory sequential design involving focus group discussions, semi-structured interviews, and perception scales administered to 87 participants (55 D.El.Ed. trainees, 24 school teachers, and 8 teacher educators) from District-East, Delhi. Qualitative data revealed major concerns such as lack of digital and physical infrastructure, language barriers in pedagogical resources, inadequate readiness among students, and heavy teacher workload due to activity-based curricula. Quantitative findings highlighted a neutral overall perception of D.El.Ed. trainees (aggregate mean = 3.33), fairly positive perceptions of teacher educators (aggregate mean = 3.94), and fairly positive perceptions of school teachers (aggregate mean = 3.90). Importantly, trainees expressed a highly positive view of enhanced training strategies (mean = 4.07), while school teachers strongly agreed that IBL improves experimental process skills and critical thinking (mean = 4.4 for learning environment). The study concludes that bridging the gap between policy intent and classroom practice requires structural reforms, early teacher preparation, and adequate infrastructural investment. Recommendations include developing bilingual/multilingual learning resources, extending DBSE training workshops, integrating simulated teaching in D.El.Ed. curricula, and strengthening digital infrastructure in government schools. This research contributes to understanding how pre-service and in-service educators can collaboratively operationalize NEP 2020’s vision of child-centric, inquiry-driven classrooms.